Wildlife trade and consumer preference for species rarity: an examination of caged-bird markets in Sumatra. (17th May 2019) - Krishna, Vijesh V.; Darras, Kevin; Grass, Ingo; Mulyani, Yeni A.; Prawiradilaga, Dewi M.; Tscharntke, Teja; Qaim, Matin
Abstract: This study examines conservation effects of wildlife trade using demand and supply data from caged-bird markets in Sumatra, Indonesia. When consumers have a strong preference for species rarity, trade could result in wildlife overexploitation and species extinction. Results from a choice experiment show that buyers of caged birds indeed value species rarity. However, not all rare species are equally preferred. Species that are frequently traded lose their rarity value, even if rare in the wild. Analysis of time-series data collected from traders over a period of 20 months between 2013 and 2015 reveals an inelastic supply function for rare species, with market arrivals being insensitive to price changes. This may be due to a declining stock of rare species in the wild. Bird trade together with habitat loss can lead to extinction of a number of rare species in Indonesia. Several policy approaches on regulating caged-bird markets are discussed.